FACULTY SATISFACTION WITH THE COMPETENCY-BASED MEDICAL EDUCATION PROGRAM AT HAI PHONG UNIVERSITY OF MEDICINE AND PHARMACY (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe faculty satisfaction with competency-based medical education program at Hai Phong University of Medicine and Pharmacy.Subjects: A total of 98 lecturers involved in teaching the competency-based medical education program at Hai Phong University of Medicine and Pharmacy.Methods: A cross-sectional descriptive study was conducted using a structured interview questionnaire.Results and conclusions: the overall satisfaction score of lecturers with the training program was 4.27 ± 0.55. Among the evaluated domains, satisfaction with “Learning outcomes” received the highest score, while “Teaching organization and assessment” received the lowest, at 4.44 ± 0.55 and 3.99 ± 0.66, respectively. There were no statistically significant differences in satisfaction score by job position, academic qualification, or teaching field. However, for the domains “Program description” and “Teaching support activities,” satisfaction scores were higher among preclinical faculty compared to clinical faculty group. Additionally, lecturers’ satisfaction with the training program showed a weak negative correlation with age and years of teaching experience.
Keywords: faculty satisfaction, competency-based medical education, training program